Understanding the effects of confinement on movement behaviors in Salvadoran children - Iraheta, Boris Evert (2025)
The problem of sedentary lifestyle in childhood is a public health problem, which is suspected to have been aggravated by the health situation, so understanding the changes in physical activity during confinement in Salvadoran children is of vital importance. This study was qualitative, with an intentional sample, made up of 5 boys and 6 girls between 7 and 10 years old from a private urban school in the Salvadoran capital. The focused interview, with an open-ended questionnaire, was the technique used. The information was analyzed with the triangulation method, using the categories of analysis of the interpersonal, intrapersonal and organizational level. The main findings showed a perception of the infants of decreased physical activity, evidencing the lack of parental support towards active behaviors, which contributed to feelings of loneliness. Social interaction was reduced to family contact, accompanied by the unlimited use of technologies, causing perceptions of isolation and loneliness. Evidently, this study has shown the negative effect of confinement on the physical and mental health of the participants.